A Literature Study: Ethical Problems in Information Technology in Identity Theft Cases - M. Yonandio Lazuardi (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2024)
Identity theft has become a major ethical and security issue in the digital era. The widespread use of information technology has enabled offenders to exploit personal information with increasing sophistication. Identity theft occurs when an individual’s personal data such as name, address, date of birth, or bank information is stolen and used without consent, often resulting in financial and reputational damage. This study identifies and analyzes ethical concerns arising from identity theft, emphasizing privacy violations and misuse of customer data. Using a literature study method, this paper reviews prior research on the causes, impacts, and mitigation of identity theft within the context of information ethics. The findings highlight that identity theft stems not only from technical vulnerabilities but also from moral negligence and weak regulatory enforcement. Strengthening data-protection policies, promoting digital ethics, and raising public awareness are essential steps toward reducing such crimes and preserving trust in information systems.